(untitled) (International Journal of Physiotherapy, 2021)
Background: Trunk muscle coordination can be improved by motor control exercise using Swiss ball exercises, trunk muscles that support the spine’s stability and mobility. In this study effect of motor control exercise using Swiss ball is compared with stretching exercise on low back pain. This study is also aimed to find the effect of motor control exercise using Swiss ball and stretching exercise within the group on mechanical low back pain. Methods: A Comparative study was done at ACS Medical College and Hospital, Chennai, with 30 samples. The duration of the treatment was four weeks. Male and female genders were selected for the study with the age of 18-25 yrs. The outcome measures were Low Back Index Scale, Quebec Disability Scale, and Schober Test. Total 30 subjects were randomly allocated, 15 in each group A and B by fulfilling inclusion criteria. Intervention for Group A trained with motor control exercise using Swiss ball and Group B with stretching exercise. Both groups receive treatment for three sessions /week of a total of 12 sessions of treatment. Results: Motor Control Exercises using Swiss Ball found more effective than stretching on reduction of pain with mean difference 2.60 and 2.533 respectively, and stretching found more effective than motor control exercise on disability and improve spinal mobility with a mean difference of 19.00, 19.67, and 22.00, 23.00 respectively among patients mechanical low back pain. Conclusion: Motor Control Exercises using Swiss Ball was found more effective than stretching to reduce pain, disability and improve spinal mobility among patients with mechanical low back pain.